Chinese language teachers' beliefs about their roles in the Danish context. (October 2016) - Wang, Li; Du, Xiangyun
Abstract: This paper focuses on how teachers of Chinese as a foreign language (CFL) perceive their roles in the Danish context. In this qualitative study of twelve native and non-native Chinese-speaking language teachers, empirical data was collected from semi-structured interviews and classroom observations to explore teachers' beliefs about their roles. The study found that most teachers saw themselves as filling multiple roles and revealed that these were defined based on the following perspectives: how teachers plan and conduct teaching activities, what they want to emphasise and achieve in teaching and their relationships with their students and work environment. These findings suggest that teachers' individual cultural backgrounds, personal experiences and contextual factors all contribute to variations in their beliefs about their roles, including how they understand their facilitator role, teach culture and build relationships with students. Research results also reveal some contextual factors that challenge teachers' beliefs about their roles, including inadequate teaching materials, limited access to professional training and students who lack motivation to learn. These factors suggest a need for institutional support in building a professional community of CFL teachers in Denmark.